Analysis of Metabolite Levels, Secondary Minerals and Aloe Vera Formulation from Kalimantan Indonesia - Fahmi Said; Ida Rahmawati; Neny Setiawaty Ningsih (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2022)
Products from natural ingredients such as aloe vera must be high quality and meet standardization aspects. Determination of secondary metabolites and mineral levels is part of the standardization of natural product products. The dosage formula needs to be optimized to get the best formula based on evaluating the physical properties of the gel preparation. This study aimed to analyze the highest mineral and metabolite content between aloe vera from South Kalimantan and West Kalimantan, as well as the optimum formula for aloe vera gel based on its physical properties. The research method used is to perform sample preparation, extraction, analysis of minerals and secondary metabolites by spectroscopy. The data were analyzed descriptively, and the results showed that the content of iron, calcium, and zinc originating from West Kalimantan was 0.314 mg/g; 93.42 mg/g; 0.059 mg/g, while South Kalimantan 0.064 mg/g, 53.24 mg/g, 0.032 mg/g. The total phenolic, flavonoid, and anthraquinone levels from West Kalimantan were 0.512%, 1.31%, respectively, 2.28%, while those from South Kalimantan were 0.321%, 1.12%, 1.14%. The best formula for aloe vera gel is formula three, which has a darker color and meets the requirements of the physical properties of the gel. This study concludes that the highest mineral content in aloe vera comes from West Kalimantan, the highest secondary metabolite content also comes from West Kalimantan. And the best formula is the third formula with 20% natural dyes. Suggestions for further research are to examine the mineral content and secondary metabolites of aloe vera in various places in Indonesia so that the best aloe vera can be known.